Battery and electric device

By adding tris(dimethylvinyl silicone) phosphate to the electrolyte of lithium iron phosphate battery and setting a positive electrode active material layer on the positive electrode sheet to control specific parameters, the serious problem of gas production in the battery is solved, and the balance of low DCR and low gas production is achieved.

CN119764591AActive Publication Date: 2025-04-04CALB GROUP CO LTD

Patent Information

Application Number
CN202411978661.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The internal gas production of lithium iron phosphate batteries has severely led to an increase in DCR, especially in lithium supplement systems.

Method used

By adding tris(dimethylvinyl silicone) phosphate to the electrolyte and setting a positive electrode active material layer on the positive electrode sheet, the contact angle and powder resistivity of the positive electrode active material layer with the solution are controlled to satisfy a specific relationship to reduce side reactions and gas production.

Benefits of technology

It achieves that the battery has few side reactions, low gas production, high ion and electron conductivity during the cycle process, and has both low gas production and low DCR.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764591A_ABST
    Figure CN119764591A_ABST
Patent Text Reader

Abstract

The invention relates to a battery and an electric device, and belongs to the technical field of batteries. The battery comprises an electrolyte and a positive pole piece, the positive pole piece comprises a positive current collector and a positive active material layer arranged on at least one surface of the positive current collector, the positive active material layer comprises a positive active material, the positive active material comprises lithium iron phosphate, and the electrolyte comprises tris (dimethyl vinyl silicon) phosphate; by regulating and controlling the mass ratio a of tris (dimethylvinylsilyl) phosphate in the electrolyte, the contact angle b of the positive active material layer and the solution and the powder resistivity c of the positive active material layer to meet a specific relational expression, the battery has few side reactions and low gas production rate in the cycle process, the ion and electron conductivity of the positive pole piece is high, and the service life of the battery is prolonged. Therefore, the low gas production rate and the low DCR can be achieved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery and an electrical device. Background Art

[0002] Lithium iron phosphate batteries have the advantages of high operating voltage, high energy density, good safety performance, low self-discharge rate, and no memory effect. However, lithium iron phosphate batteries produce serious gas inside. Adding phosphate additives to the electrolyte can inhibit gas production, but this will increase the DCR of the battery, especially in the lithium supplement system (i.e., the positive electrode contains lithium supplement additives). Summary of the invention

[0003] The object of the present invention is to overcome the above-mentioned deficiencies of the prior art and provide a battery and an electrical device so that the lithium iron phosphate battery has both low gas production and low DCR.

[0004] To achieve the above-mentioned object, in a first aspect, the present invention provides a battery, comprising an electrolyte and a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, wherein the positive electrode active material comprises lithium iron phosphate, and the electrolyte comprises tris(dimethylvinylsilyl)phosphate;

[0005] The battery satisfies the following relationship: 0.3<a×b×c<124,

[0006] Wherein, a is the mass proportion of the tris(dimethylvinylsilyl)phosphate in the electrolyte;

[0007] b is the contact angle between the positive electrode active material layer and the solution, in degrees, wherein the solution consists of ethylene carbonate, ethyl methyl carbonate and lithium hexafluorophosphate, wherein the mass ratio of ethylene carbonate to ethyl methyl carbonate is 3:7, and the concentration of lithium hexafluorophosphate in the solution is 1 mol / L;

[0008] c is the powder resistivity of the positive electrode active material layer, in Ω·cm.

[0009] In a second aspect, the present invention provides an electrical device comprising the battery.

[0010] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adjusts the mass proportion of tri(dimethylvinylsilyl)phosphate in the electrolyte, the contact angle between the positive electrode active material layer and the solution, and the powder resistivity of the positive electrode active material layer to satisfy a specific relationship, so that the battery has fewer side reactions during the cycle, low gas production, and high ionic and electronic conductivity of the positive electrode plate, thereby achieving both low gas production and low DCR. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is an experimental diagram of Example 1 when testing the contact angle b between the positive electrode active material layer and the solution. DETAILED DESCRIPTION

[0012] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0013] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0014] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0015] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0016] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0017] Battery

[0018] The present invention provides a positive electrode plate, comprising an electrolyte and a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, wherein the positive electrode active material comprises lithium iron phosphate, and the electrolyte comprises tris(dimethylvinylsilyl)phosphate (DMVSP);

[0019] The battery satisfies the following relationship: 0.3<a×b×c<124,

[0020] Wherein, a is the mass proportion of the tris(dimethylvinylsilyl)phosphate in the electrolyte;

[0021] b is the contact angle between the positive electrode active material layer and the solution, in degrees, wherein the solution consists of ethylene carbonate, ethyl methyl carbonate and lithium hexafluorophosphate, wherein the mass ratio of ethylene carbonate to ethyl methyl carbonate is 3:7, and the concentration of lithium hexafluorophosphate in the solution is 1 mol / L;

[0022] c is the powder resistivity of the positive electrode active material layer, in Ω·cm.

[0023] By rationally controlling the mass proportion of DMVSP in the electrolyte, the contact angle between the positive electrode active material layer and the solution, and the powder resistivity of the positive electrode active material layer, the battery can have fewer side reactions during the cycle, low gas production, and high ionic and electronic conductivity of the positive electrode sheet, thereby achieving both low gas production and low DCR.

[0024] The value of the mass proportion (a) of DMVSP in the electrolyte affects the gas production and DCR of the battery. Increasing the mass proportion (a) of DMVSP in the electrolyte is beneficial to improving the gas production problem of the battery, but will lead to an increase in the DCR of the battery. The value of the mass proportion (a) of DMVSP in the electrolyte can be adjusted by adjusting the ratio of the electrolyte and DMVSP.

[0025] The present invention does not limit the detection method of the mass ratio (a) of DMVSP in the electrolyte. Those skilled in the art can detect the mass ratio (a) of DMVSP in the electrolyte according to conventional technical means. Exemplarily, the mass ratio (a) of DMVSP in the electrolyte can be detected by the following method:

[0026] Use battery charging and discharging equipment to discharge the battery. Discharging conditions: current 0.33C, cut-off voltage 2.5V, record the battery number / barcode;

[0027] The battery was disassembled and the electrolyte was collected in a glove box (internal environment met: H2O≤0.1ppm, O2≤0.1ppm);

[0028] A nuclear magnetic resonance spectrometer is used to test whether DMVSP exists in the electrolyte. If it exists, a gas chromatograph is used to test the mass ratio of DMVSP in the electrolyte.

[0029] Among them, disassembling the battery and collecting the electrolyte can be carried out according to the following three methods:

[0030] ① After removing the battery cover, if there is enough (i.e. more than 10 mL, the same below) free electrolyte, use a pipette to collect the electrolyte into the sample tube and seal it with sealing film;

[0031] ② After removing the battery cover, if there is not enough free electrolyte, you can use a hydraulic press (such as the FY-30 hydraulic press of Beijing Hengaode Technology Co., Ltd.) to continuously pressurize until free electrolyte appears, collect the electrolyte into the sample tube and seal it with a sealing film;

[0032] ③ After removing the battery cover, if both method ① and method ② fail to collect enough electrolyte, an extraction experiment is required. The specific operation is as follows: add 2-5g / Ah of a mixture of dichloromethane and cyclohexylbenzene (the volume ratio of the two is 1:9) as an extractant to the battery and record the amount of the extractant. Then put the battery into an aluminum-plastic bag and seal it with a heat sealer. Let it stand at room temperature of 25°C for 4 days to allow the electrolyte in the electrode to be fully mixed with dichloromethane. Then use a pipette to draw the mixture of the extractant and the electrolyte into a 5mL sample tube, and seal the sample tube with a sealing film.

[0033] The mass proportion of DMVSP in the electrolyte can be tested using a gas chromatograph (Thermo Fisher Trace-1610) as follows: the collected electrolyte sample is injected into a 2 mL injection bottle using a microinjector, the response curve of the electrolyte sample is tested, and compared with the DMVSP standard curve (the same test is performed using pure DMVSP to obtain the standard curve) to obtain the mass proportion of DMVSP in the electrolyte.

[0034] The method for using a nuclear magnetic resonance spectrometer to test whether DMVSP exists in the electrolyte is as follows: 1 mL of the collected electrolyte sample is placed in a sample tube, 0.5 mL of CDCl3 (deuterated chloroform) is taken with a syringe and injected into the sample tube to fully dissolve the sample, and a nuclear magnetic resonance spectrometer (Bruker 400 MHz nuclear magnetic resonance NMR spectrometer) is used to test the nuclear magnetic resonance spectrum of the electrolyte, and compared with the DMVSP standard curve (the same test is performed using pure DMVSP to obtain a standard curve) to assist in confirming whether DMVSP exists in the electrolyte.

[0035] Lithium iron phosphate batteries often use a mixed solution of ethylene carbonate and ethyl methyl carbonate with lithium hexafluorophosphate added as the electrolyte. The contact angle (b) between the positive electrode active material layer and the solution reflects the wettability of the positive electrode plate to the electrolyte. The reduction of the contact angle (b) between the positive electrode active material layer and the solution can improve the wettability of the positive electrode plate to the electrolyte. On the one hand, this helps to reduce the ionic impedance of the positive electrode plate and thus reduce the DCR of the battery; on the other hand, it increases the contact area between the electrolyte and the positive electrode plate. The contact angle (b) between the positive electrode active material layer and the solution can be adjusted by adjusting the type and / or amount of carbon source in the carbon coating process of the positive electrode active material and the compaction density of the positive electrode plate.

[0036] The present invention does not limit the detection method of the contact angle (b) between the positive electrode active material layer and the solution. Those skilled in the art can detect the contact angle (b) between the positive electrode active material layer and the solution according to conventional technical means. Exemplarily, the contact angle (b) between the positive electrode active material layer and the solution can be measured using a contact angle meter (Beijing Zhongyi Kexin Technology Co., Ltd. JC2000D2M), and the specific test method is as follows:

[0037] 1) Pretreatment of positive electrode sheet: After disassembling the empty battery, use ceramic scissors to cut the positive electrode sheet of about 8.5*8cm in size. After placing the positive electrode sheet at room temperature of 25℃ for 6 to 10 hours, the two ends of the electrode sheet can be fixed on the test fixture to start the test;

[0038] 2) Place the device for fixing the electrode on the sample placement table of the contact angle measuring instrument;

[0039] 3) dropping the solution onto the electrode with a syringe, measuring the contact angle of the solution dropped on the electrode within 0.01 to 0.05 s, and calculating the contact angle using a five-point fitting method and an image analysis method; wherein the solution is prepared by mixing ethylene carbonate EC and ethyl methyl carbonate EMC in a mass ratio of 3:7, adding lithium hexafluorophosphate, and adjusting the concentration of the lithium hexafluorophosphate to 1 mol / L.

[0040] The powder resistivity (c) of the positive electrode active material layer is related to the electronic conductivity of the positive electrode sheet and the wettability of the positive electrode sheet to the electrolyte. Reducing the powder resistivity (c) of the positive electrode active material layer can improve the electronic conductivity of the positive electrode sheet, improve the DCR of the battery, and also improve the wettability of the positive electrode sheet to the electrolyte. The powder resistivity (c) of the positive electrode active material layer can be adjusted by adjusting the particle size of the positive electrode powder and the ratio of the conductive agent and the binder in the positive electrode slurry.

[0041] The present invention does not limit the detection method of the powder resistivity (c) of the positive electrode active material layer. Those skilled in the art can detect the powder resistivity (c) of the positive electrode active material layer according to conventional technical means. Exemplarily, the powder resistivity (c) of the positive electrode active material layer can be detected by the following method:

[0042] The battery was discharged at 0.33C and disassembled. The positive electrode was placed in a fume hood for 24 hours. 1 g of positive electrode powder was collected with a scraper. The scraped positive electrode powder was ball-milled at a speed of 300 r / min. The ball used for ball milling was a zirconia ball with a diameter of 0.6 mm. The ball-to-material ratio was 5:1 and the ball milling time was 20 to 40 min. After ball milling, the powder was placed in a four-probe resistivity tester (such as the ST2722 semiconductor powder resistivity tester of Suzhou Jingge Electronics Co., Ltd.) for powder resistivity test. The specific operation method is as follows: Place the powder on the electrode and pressurize the powder with the other side electrode. The pressure strength is 10 MPa. Read the value of the powder resistivity.

[0043] The mass proportion of DMVSP in the electrolyte, the contact angle between the positive electrode active material layer and the solution, and the powder resistivity of the positive electrode active material layer all affect the DCR and gas production of the battery to varying degrees, and have certain mutual influences. It is difficult to achieve both low DCR and low gas production in the battery by controlling a single variable. The present invention adjusts the mass proportion of DMVSP in the electrolyte, the contact angle between the positive electrode active material layer and the solution, and the powder resistivity of the positive electrode active material layer to meet the above-mentioned specific relationship, so that the battery has fewer side reactions during the cycle, low gas production, and high ionic and electronic conductivity of the positive electrode sheet, so that it can have both low gas production and low DCR.

[0044] Exemplarily, the value of a×b×c can be selected to be 0.4, 0.6, 0.8, 1.0, 1.1, 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 115, 120, 123 or an interval formed by any two of the above values.

[0045] In one preferred embodiment, the battery satisfies the following relationship: 0.5≤a×b×c≤16. The value of a×b×c is controlled within this range to make the DCR of the battery lower, the side reactions less, and the gas production lower.

[0046] In some embodiments, the positive electrode active material layer further includes a lithium supplement additive.

[0047] In one preferred embodiment, the lithium supplement additive includes lithium-rich iron oxide (LFO). When the lithium supplement additive includes lithium-rich iron oxide, the empty battery is disassembled, the positive electrode is taken out, washed with DMC (dimethyl carbonate) for 4-5 hours, and then left to stand at 45°C for 3 hours. XPS (X-ray photoelectron spectroscopy) is used to detect that the positive electrode contains Fe. 4+ .

[0048] In one embodiment, the mass ratio of the lithium supplement additive in the positive electrode active material layer is 0.001 to 0.05. For example, the mass ratio of the lithium supplement additive in the positive electrode active material layer is 0.001, 0.003, 0.005, 0.007, 0.01, 0.02, 0.03, 0.04, 0.05, or an interval formed by any two of the above values.

[0049] In some embodiments, the positive electrode active material further includes at least one of lithium iron manganese phosphate and a ternary material. When the positive electrode active material includes at least one of lithium iron manganese phosphate and a ternary material, the upper limit voltage of the positive electrode plate can be increased. The sum of the mass proportions of the lithium iron manganese phosphate and the ternary material in the positive electrode active material layer is 0.02 to 0.5, such as 0.02, 0.05, 0.07, 0.1, 0.2, 0.3, 0.4, 0.5 or the interval formed by any two of the above values.

[0050] The mass ratio of the lithium manganese iron phosphate in the positive electrode active material layer can be selected to be 0.02-0.5, such as 0.02, 0.05, 0.07, 0.1, 0.2, 0.3, 0.4, 0.5 or an interval formed by any two of the above values; the chemical formula of the lithium manganese iron phosphate is LiMn e Fe 1-e PO4, 0<e<1, such as 0.01, 0.03, 0.05, 0.07, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.93, 0.96, 0.99 or the interval formed by any two of the above values; the particle size Dv50 of the lithium manganese iron phosphate is 2-3μm, such as 2μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3μm or the interval formed by any two of the above values. The present invention does not limit the detection method of the particle size Dv50 of lithium manganese iron phosphate, and those skilled in the art can detect the particle size Dv50 of lithium manganese iron phosphate according to conventional technical means. Exemplarily, the particle size Dv50 of lithium iron manganese phosphate can be detected by the following method: discharge the battery at 0.33C to a voltage of 2.5V, disassemble it, place the positive electrode plate in a fume hood for 24 hours, then collect 0.1-0.2g of positive electrode powder with a scraper, photograph the obtained positive electrode powder with a scanning electron microscope (SEM), measure the lithium iron manganese phosphate particle size of the positive electrode powder in the SEM image with MEARSURE NANO software, collect the lithium iron manganese phosphate particle size using the diagonal stroke method, and after the sample size reaches more than 100, statistically analyze the particle size distribution and calculate the particle size-related parameters of lithium iron manganese phosphate: Dv50.

[0051] The mass proportion of the ternary material in the positive electrode active material layer can be selected to be 0.02-0.5, such as 0.02, 0.05, 0.07, 0.1, 0.2, 0.3, 0.4, 0.5 or an interval formed by any two of the above values; the ternary material is LiNi x Co y Mn (1-x-y) O2, where 0<x<1 (such as 0.01, 0.03, 0.05, 0.07, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.93, 0.96, 0.99 or the interval formed by any two of the above values), 0<y<1 (such as 0.01, 0.03, 0.05, 0.07, 0.1, 0.2, 0. 3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.93, 0.96, 0.99 or the interval formed by any two of the above values); the particle size Dv50 of the ternary material is 3 to 20 μm, such as 3 μm, 5 μm, 7 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm or the interval formed by any two of the above values. The present invention does not limit the detection method of the particle size Dv50 of the ternary material, and those skilled in the art can detect the particle size Dv50 of the ternary material according to conventional technical means. Exemplarily, the particle size Dv50 of the ternary material can be detected by the following method: discharge the battery at 0.33C to a voltage of 2.5V, disassemble it, place the positive electrode plate in a fume hood for 24 hours, then collect 0.1-0.2g of positive electrode powder with a scraper, photograph the obtained positive electrode powder with a scanning electron microscope (SEM), measure the particle size of the ternary material of the positive electrode powder in the SEM image with MEARSURE NANO software, and collect the particle size of the ternary material using the diagonal stroke method. After the sample size reaches more than 100, the particle size distribution is statistically analyzed to calculate the particle size related parameters of the ternary material: Dv50.

[0052] In some embodiments, c is 1 to 200 Ω·cm. For example, c is 1 Ω·cm, 3 Ω·cm, 5 Ω·cm, 7 Ω·cm, 10 Ω·cm, 15 Ω·cm, 20 Ω·cm, 25 Ω·cm, 30 Ω·cm, 35 Ω·cm, 40 Ω·cm, 45 Ω·cm, 50 Ω·cm, 60 Ω·cm, 70 Ω·cm, 80 Ω·cm, 90 Ω·cm, 100 Ω·cm, 110 Ω·cm, 120 Ω·cm, 130 Ω·cm, 140 Ω·cm, 150 Ω·cm, 160 Ω·cm, 170 Ω·cm, 180 Ω·cm, 190 Ω·cm, 200 Ω·cm, or an interval formed by any two of the above values.

[0053] When c is in the range of 1 to 200 Ω·cm, not only is the wettability of the positive electrode plate to the electrolyte within a more reasonable range, there are fewer side reactions between the positive electrode plate and the electrolyte, the gas production is less, and the electronic conductivity of the positive electrode plate is higher, and the DCR of the battery is lower.

[0054] In one preferred embodiment, the c is 5 to 50 Ω·cm. When the c is within this range, it is more conducive to the balance between the gas production and DCR of the battery.

[0055] In some embodiments, b is 10° to 40°. For example, b is 10°, 13°, 15°, 17°, 20°, 22°, 25°, 28°, 30°, 32°, 35°, 37°, 40°, or an interval formed by any two of the above values.

[0056] When b is in the range of 10° to 40°, the wetting rate of the positive electrode plate to the electrolyte is in a more reasonable range. Not only is the positive electrode plate less likely to have side reactions with the electrolyte, but the ionic impedance inside the battery is lower and the DCR of the battery is lower.

[0057] In some embodiments, a is 0.0001 to 0.05. For example, a is 0.0001, 0.0005, 0.001, 0.005, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, or an interval formed by any two of the above values.

[0058] When a is in the range of 0.0001 to 0.05, the gas production of the battery is small and the DCR of the battery is lower.

[0059] In one preferred embodiment, a is 0.001 to 0.01. When a is within this range, it is more conducive to the balance between the gas production and DCR of the battery.

[0060] In some embodiments, the particle size Dv50 of the lithium iron phosphate is 0.1 to 2 μm, such as 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, 1.2 μm, 1.5 μm, 1.7 μm, 2 μm or an interval formed by any two of the above values. The particle size Dv50 of the lithium iron phosphate is controlled within this specific range so that the contact angle of the solution on the surface of the positive electrode plate is within a suitable range, while maintaining good porosity in the positive electrode active material layer, increasing the wetting rate of the electrolyte to the positive electrode plate, and reducing ionic impedance. The present invention does not limit the detection method of the particle size Dv50 of the lithium iron phosphate, and those skilled in the art can detect the particle size Dv50 of the lithium iron phosphate according to conventional technical means. Exemplarily, the particle size Dv50 of lithium iron phosphate can be detected by the following method: discharge the battery at 0.33C to a voltage of 2.5V, disassemble it, place the positive electrode plate in a fume hood for 24 hours, then collect 0.1-0.2g of positive electrode powder with a scraper, photograph the obtained positive electrode powder with a scanning electron microscope (SEM), measure the lithium iron phosphate particle size of the positive electrode powder in the SEM image with MEARSURE NANO software, collect the lithium iron phosphate particle size using the diagonal stroke method, and after the sample size reaches more than 100, statistically analyze the particle size distribution and calculate the particle size-related parameters of lithium iron phosphate: Dv50.

[0061] In some embodiments, the compaction density of the positive electrode sheet is 2.0 to 3.0 g / cm 3 , such as 2.0g / cm 3 , 2.2g / cm 3 , 2.4g / cm 3 , 2.6g / cm 3 , 2.8g / cm 3 、3.0g / cm 3 Or the interval formed by any two of the above values. When the compaction density of the positive electrode sheet is controlled within this specific range, the surface of the positive electrode sheet has better wettability to the electrolyte, which can reduce the ionic impedance of the entire battery. At the same time, since the surface density is within a suitable range, the energy density of the battery is well guaranteed.

[0062] The present invention does not limit the detection method of the compaction density of the positive electrode sheet. Those skilled in the art can detect the compaction density of the positive electrode sheet according to conventional technical means. Exemplarily, the compaction density of the positive electrode sheet can be detected by the following method:

[0063] The battery was discharged at 0.33C with a cut-off voltage of 2.5V. After disassembling the battery, the positive electrode sheet was taken out and placed in a fume hood for 24 hours. The positive electrode sheet was cut into discs with a diameter of 4 cm, and the mass of the original sheet was recorded as m1 and the area as s1. The mass of the positive electrode foil of the same size was measured as m2, and the surface density d was calculated according to the formula d = (m1-m2) / s1. The thickness of the positive active material layer in the positive electrode disc was measured as h1, and the compaction density was calculated according to the formula compaction density = d / h1.

[0064] In some embodiments, the mass ratio of the positive electrode active material in the positive electrode active material layer is 0.95-0.998, such as 0.95, 0.955, 0.96, 0.965, 0.97, 0.975, 0.98, 0.985, 0.99, 0.995, 0.998 or an interval formed by any two of the above values.

[0065] The positive electrode active material layer further includes a conductive agent and a binder in addition to the positive electrode active material.

[0066] The conductive agent in the positive electrode active material layer is used to provide conductivity, and any conductive agent can be used without particular limitation, as long as it has suitable electronic conductivity and does not significantly cause adverse chemical changes in the battery. Exemplarily, the conductive agent in the positive electrode active material layer includes, but is not limited to, at least one of carbon nanotubes, carbon black, graphite, carbon fiber, activated carbon, mesoporous carbon, and fullerenes, wherein the carbon fiber is such as carbon nanofiber, etc.; carbon black is such as acetylene black, Ketjen black, SuperP (i.e., SP), etc.

[0067] In some embodiments, the mass ratio of the conductive agent in the positive electrode active material layer is 0.001-0.02, such as 0.001, 0.003, 0.005, 0.007, 0.01, 0.012, 0.015, 0.017, 0.02 or an interval formed by any two of the above values.

[0068] The binder in the positive electrode active material layer is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode current collector. Any binder can be used without particular limitation, as long as it has suitable binder properties and does not significantly cause adverse chemical changes in the battery. Exemplarily, the binder in the positive electrode active material layer includes but is not limited to fluorinated polyolefin binders, and the fluorinated polyolefin binders include but are not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (e.g., carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives, etc.

[0069] In some embodiments, the binder has a mass ratio of 0.001 to 0.05 in the positive electrode active material layer, such as 0.001, 0.003, 0.005, 0.007, 0.01, 0.02, 0.03, 0.04, 0.05 or an interval formed by any two of the above values.

[0070] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: aluminum, nickel, titanium, stainless steel, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.

[0071] The method for preparing the positive electrode active material is not particularly limited in the present invention, and those skilled in the art can prepare the positive electrode active material by conventional means.

[0072] Exemplarily, the preparation method of the positive electrode active material can be prepared by the following method:

[0073] The iron phosphate, carbon source and lithium carbonate are mixed in an organic solvent in a mass ratio of 1: (0.15-0.35): 0.09, and spray-dried to obtain a raw material. The raw material is sintered at a temperature of 650-800°C for 1-5 hours to obtain a positive electrode active material. The carbon source can be selected to include at least one of glucose, sucrose and polyethylene glycol. The organic solvent can be selected to include at least one of methanol and ethanol. After sintering, grinding or grinding and screening can also be performed.

[0074] Exemplarily, the preparation method of the positive electrode active material can also be prepared by the following method: iron phosphate and lithium carbonate are mixed in an organic solvent at a mass ratio of 1:0.09, spray dried to obtain raw materials, and the raw materials are sintered at a temperature of 650 to 800 ° C for 1 to 5 hours to obtain the positive electrode active material. Among them, the organic solvent can be selected to include at least one of methanol and ethanol. After sintering, grinding, or grinding and sieving can also be performed. The positive electrode active material can also directly use commercially available lithium iron phosphate, such as directly using lithium iron phosphate from Beijing Dangsheng Materials Technology Co., Ltd.

[0075] The positive electrode active material can also be prepared by the following method: mixing lithium iron phosphate with at least one of lithium iron manganese phosphate and ternary materials. The lithium iron phosphate here can be directly commercially available lithium iron phosphate, such as lithium iron phosphate from Beijing Dangsheng Materials Technology Co., Ltd., or can be prepared by the method in the above example.

[0076] The preparation method of the positive electrode sheet is not particularly limited in the present invention, and those skilled in the art can prepare the positive electrode sheet by conventional means. For example, the preparation method of the positive electrode sheet includes the following steps:

[0077] Disperse the positive electrode active material, conductive agent and binder in a solvent. The solvent can be N-methylpyrrolidone (NMP) or deionized water to form a uniform positive electrode slurry. Coating the positive electrode slurry on the positive electrode current collector, and after processes such as rolling, the positive electrode sheet is obtained.

[0078] The battery of the present invention further includes a negative electrode sheet, and the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector.

[0079] The present invention has no particular limitation on the negative electrode active material. Exemplarily, the negative electrode active material includes but is not limited to natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, SiO g (0 < g < 2, such as g = 1), silicon carbide, Li4Ti5O 12 and at least one of them.

[0080] In some embodiments, the mass ratio of the negative electrode active material in the negative electrode active material layer is 0.93 to 0.998, such as 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 0.993, 0.995, 0.998 or the range formed by any two of the above values.

[0081] In some embodiments, the negative electrode active material includes graphite, and the particle size Dv50 of the graphite is 5 to 20 μm, such as 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 20 μm, 22 μm, 25 μm or the range formed by any two of the above values.

[0082] The negative electrode active material layer may further contain a conductive agent and / or a binder.

[0083] The conductive agent in the negative electrode active material layer is used to provide conductivity, and any conductive agent can be used without particular limitation as long as it has suitable electronic conductivity and does not significantly cause adverse chemical changes in the battery. Exemplarily, the conductive agent in the negative electrode active material layer includes but is not limited to at least one of carbon nanotubes, carbon black, graphite, carbon fiber, activated carbon, mesoporous carbon, fullerenes, etc. Among them, carbon fiber such as carbon nanofiber, etc.; carbon black such as acetylene black, Ketjen black, Super P (i.e., SP), etc.

[0084] In some embodiments, based on the weight of the negative electrode active material layer, the mass proportion of the conductive agent in the negative electrode active material layer is 0.001-0.02, such as 0.001, 0.003, 0.005, 0.007, 0.01, 0.012, 0.014, 0.016, 0.018, 0.02 or an interval formed by any two of the above values.

[0085] The binder in the negative electrode active material layer is used to improve the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material and the negative electrode current collector. Any binder can be used without special restrictions, as long as it has suitable binding properties and does not significantly cause adverse chemical changes in the battery. Exemplarily, the binder in the negative electrode active material layer includes but is not limited to at least one of carboxymethyl cellulose (CMC), styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, and water-based acrylic resin.

[0086] In some embodiments, based on the weight of the negative electrode active material layer, the mass proportion of the binder in the negative electrode active material layer is 0.001-0.05, such as 0.001, 0.003, 0.005, 0.007, 0.01, 0.02, 0.03, 0.04, 0.05 or an interval formed by any two of the above values.

[0087] The present invention has no particular limitation on the negative electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with at least one of carbon, nickel, titanium, silver, etc., or aluminum-cadmium alloy.

[0088] The method for preparing the negative electrode sheet is not particularly limited in the present invention, and a person skilled in the art can prepare the negative electrode sheet by conventional means. For example, the method for preparing the negative electrode sheet includes the following steps:

[0089] The negative electrode active material, conductive agent and binder are dispersed in a solvent, which may be N-methylpyrrolidone (NMP) or deionized water, to form a uniform negative electrode slurry, which is then coated on a negative electrode current collector, and after processes such as rolling, a negative electrode sheet is obtained.

[0090] The electrolyte of the present invention also includes a solvent. Exemplary, the solvent includes but is not limited to ethylene carbonate (EC), methylene methanedisulfonate (MMDS), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propylene carbonate (PC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), at least one of diethyl sulfone (ESE).

[0091] The mass proportion of the solvent in the electrolyte can be selected to be 0.65-0.98889, such as 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 0.98, 0.9889 or an interval formed by any two of the above values.

[0092] In some embodiments, the electrolyte further comprises methylene methanedisulfonate, and the mass proportion of methylene methanedisulfonate in the electrolyte is 0.00001 to 0.05, such as 0.00001, 0.00005, 0.0001, 0.0005, 0.001, 0.005, 0.01, 0.03, 0.05, or an interval formed by any two of the above values. Adding the above specific amount of methylene methanedisulfonate can reduce the amount of DMVSP used and further reduce the ionic resistance.

[0093] The electrolyte also includes an electrolyte, which may generally include a lithium salt. Exemplarily, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalate phosphate) (LiDFOP), lithium tetrafluorooxalate phosphate (LiTFOP). The mass ratio of the electrolyte in the electrolyte may be selected to be 0.01 to 0.2, such as 0.01, 0.03, 0.05, 0.07, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2 or at least one of any two of the above values.

[0094] In addition, the electrolyte may also contain other additives. Exemplarily, the other additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery high temperature performance, additives that improve battery overcharge performance, and additives that improve battery low temperature performance.

[0095] The preparation method of the electrolyte is not particularly limited in the present invention, and those skilled in the art can prepare the negative electrode sheet by conventional means. For example, the preparation method of the electrolyte includes the following steps:

[0096] The solvent, lithium salt, DMVSP and other additives (if any) are mixed to obtain an electrolyte.

[0097] The battery may further include a diaphragm, which is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The diaphragm may be any isolation film material suitable for batteries in the art. Exemplarily, the diaphragm includes but is not limited to at least one of polypropylene (PP) and polyethylene (PE).

[0098] Electrical devices

[0099] The present invention also provides an electric device, comprising the battery. The battery serves as a power supply for the electric device.

[0100] The power-consuming device refers to any device that can utilize electrical energy and convert it into other forms of energy such as mechanical energy, thermal energy, light energy, etc. The other forms of energy converted can be one or more. Exemplarily, the power-consuming device includes at least one of electric vehicles, electric trains, mobile devices, ships and satellites, energy storage systems, etc. For example, the electric vehicles include but are not limited to pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.; the mobile devices include but are not limited to mobile phones, laptops, drones, sweeping robots, etc.

[0101] The present invention is further described below with reference to specific embodiments.

[0102] Example 1

[0103] Embodiment 1 provides a battery, and its preparation method is as follows:

[0104] (1) Preparation of positive electrode sheet

[0105] (1.1) Preparation of lithium iron phosphate

[0106] Iron phosphate, carbon source and lithium carbonate are mixed in methanol at a mass ratio of 1:0.25:0.09, and spray-dried to obtain raw materials. The raw materials are sintered at 700°C for 3 hours, ball-milled (ball-milling conditions use 0.6mm diameter zirconia balls, ball-to-material ratio of 5:1, rotation speed of 300r / min), and sieved to obtain carbon-coated lithium iron phosphate, that is, lithium iron phosphate, wherein the carbon source is glucose.

[0107] (1.2) Preparation of positive electrode

[0108] The obtained lithium iron phosphate was used as the positive electrode active material, and the positive electrode active material, the conductive agent acetylene black and the binder PVDF were mixed in a mass ratio of 96.3:0.7:3.0, and then dispersed in NMP to obtain a positive electrode slurry, which was coated on both sides of an aluminum foil, and the wet film thickness of the positive electrode slurry coated on one side of the aluminum foil was controlled to be 120 μm, and then rolled and cut to obtain a positive electrode sheet. The compaction density of the obtained positive electrode sheet is shown in Table 1.

[0109] (2) Preparation of negative electrode sheet

[0110] Artificial graphite, binder carboxymethyl cellulose and conductive agent conductive carbon black are dispersed in deionized water in a mass ratio of 95.8:1.2:3.0 to prepare a negative electrode slurry, and the negative electrode slurry is coated on both sides of the copper foil, and the wet film thickness of the negative electrode slurry coated on one side of the copper foil is controlled to be 180 μm; then rolling and cutting are performed to obtain negative electrode sheets.

[0111] (3) Preparation of electrolyte

[0112] The solvent, tris(dimethylvinylsilyl)phosphate and lithium hexafluorophosphate are mixed in a mass ratio of 0.9599:0.0051:0.035 to obtain an electrolyte;

[0113] The preparation method of the solvent is as follows: ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:4:3 to obtain the solvent.

[0114] (4) Preparation of isolation membrane

[0115] Using PE diaphragm.

[0116] (5) Assembly and formation

[0117] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0118] Examples 2 to 17 and Comparative Examples 1 to 4

[0119] Examples 2 to 17 and Comparative Examples 1 to 4 respectively provide a battery, and the preparation method is similar to that of Example 1, except that:

[0120] In step (1.1), the mass ratio of iron phosphate, carbon source and lithium carbonate and the ball milling and screening process are adjusted. The mass ratio of iron phosphate, lithium carbonate and carbon source and the particle size Dv50 of the obtained lithium iron phosphate are shown in Table 1;

[0121] In step (1.2), the mass ratio of the positive electrode active material, the conductive agent and the binder and the compaction density of the obtained positive electrode sheet are shown in Table 1;

[0122] In step (3), the mass proportion of DMVSP in the electrolyte is adjusted, and the mass proportion of the solvent in the electrolyte is adjusted accordingly. The mass proportion of DMVSP in the electrolyte is shown in Table 1.

[0123] Example 18 and Comparative Examples 7-8

[0124] Example 18 and Comparative Examples 7-8 respectively provide a battery, and the preparation method is similar to that of Example 1, except that:

[0125] In step (1.1), the ball milling and screening process was adjusted, and the particle size Dv50 of the obtained lithium iron phosphate is shown in Table 1;

[0126] In step (1.2), the obtained lithium iron phosphate and lithium iron manganese phosphate are used as positive electrode active materials, the weight of lithium iron manganese phosphate is 5% of the weight of lithium iron phosphate, and the chemical formula of the lithium iron manganese phosphate used is LiMn 0.4 Fe 0.6 PO4 and the particle size Dv50 is 2.6 μm, the mass ratio of the positive electrode active material, the conductive agent and the binder, and the compaction density of the obtained positive electrode sheet are shown in Table 1;

[0127] In step (3), the mass proportion of DMVSP in the electrolyte is adjusted, and the mass proportion of the solvent in the electrolyte is adjusted accordingly. The mass proportion of DMVSP in the electrolyte is shown in Table 1.

[0128] Example 19 and Comparative Examples 9-10

[0129] Example 19 and Comparative Examples 9-10 respectively provide a battery, and the preparation method is similar to that of Example 1, except that:

[0130] In step (1.1), the ball milling and screening process was adjusted, and the particle size Dv50 of the obtained lithium iron phosphate is shown in Table 1;

[0131] In step (1.2), the obtained lithium iron phosphate is used together with the ternary material as the positive electrode active material, the weight of the ternary material is 5% of the weight of the lithium iron phosphate, and the chemical formula of the ternary material used is LiNi0.2 Co 0.3 Mn 0.5 O2 and the particle size Dv50 is 13 μm, the mass ratio of the positive electrode active material, the conductive agent and the binder and the compaction density of the obtained positive electrode sheet are shown in Table 1;

[0132] In step (3), the mass proportion of DMVSP in the electrolyte is adjusted, and the mass proportion of the solvent in the electrolyte is adjusted accordingly. The mass proportion of DMVSP in the electrolyte is shown in Table 1.

[0133] Examples 20-21 and Comparative Examples 5-6

[0134] Examples 20-21 and Comparative Examples 5-6 respectively provide a battery, and the preparation method is similar to that of Example 1, except that:

[0135] In step (1.1), the ball milling and screening process was adjusted, and the particle size Dv50 of the obtained lithium iron phosphate is shown in Table 1;

[0136] In step (1.2), the positive electrode active material, the lithium supplement additive, the conductive agent acetylene black and the binder PVDF are mixed to prepare the positive electrode slurry. The mass ratio of the positive electrode active material, the lithium supplement additive, the conductive agent and the binder and the compaction density of the obtained positive electrode sheet are shown in Table 1, wherein the lithium supplement additive is lithium-rich lithium ferrite;

[0137] In step (3), the mass proportion of DMVSP in the electrolyte is adjusted, and the mass proportion of the solvent in the electrolyte is adjusted accordingly. The mass proportion of DMVSP in the electrolyte is shown in Table 1.

[0138] Embodiment 22

[0139] Example 22 provides a battery, the preparation method of which is similar to that of Example 1, except that:

[0140] In step (1.1), the ball milling and screening process was adjusted, and the particle size Dv50 of the obtained lithium iron phosphate is shown in Table 1;

[0141] In step (1.2), the compaction density of the obtained positive electrode sheet is shown in Table 1;

[0142] In step (3), the solvent, tris(dimethylvinylsilyl)phosphate, lithium hexafluorophosphate and methylene disulfonate are mixed to prepare an electrolyte. The mass proportion of DMVSP in the electrolyte is shown in Table 1, the mass proportion of methylene disulfonate in the electrolyte is 0.003, and the mass proportion of lithium hexafluorophosphate in the electrolyte remains unchanged.

[0143] Examples 23 to 27 and Comparative Examples 11 to 12

[0144] Examples 23 to 27 and Comparative Examples 11 to 12 respectively provide a battery, and the preparation method is similar to that of Example 1, except that:

[0145] In step (1.1), no carbon source was used, the ball milling and screening process was adjusted, and the mass ratio of iron phosphate to lithium carbonate and the particle size Dv50 of the obtained lithium iron phosphate were shown in Table 1;

[0146] In step (1.2), the mass ratio of the positive electrode active material, the conductive agent and the binder and the compaction density of the obtained positive electrode sheet are shown in Table 1;

[0147] In step (3), the mass proportion of DMVSP in the electrolyte is adjusted, and the mass proportion of the solvent in the electrolyte is adjusted accordingly. The mass proportion of DMVSP in the electrolyte is shown in Table 1.

[0148] The following method was used to detect the mass proportion a of DMVSP in the electrolyte, the contact angle b between the positive electrode active material layer and the solution, and the powder resistivity c of the positive electrode active material layer in each embodiment and comparative example. The test results are shown in Table 1:

[0149] (1) Mass proportion of DMVSP in the electrolyte a

[0150] Discharge the battery under the following conditions: current 0.33C, discharge cut-off voltage 2.5V, record the battery number / barcode; disassemble the battery in a glove box (internal environment meets: H2O≤0.1ppm, O2≤0.1ppm), remove the battery cover, and collect the electrolyte according to methods ① to ③:

[0151] ① If there is enough free electrolyte (i.e. more than 10 mL, the same below), use a pipette to collect the electrolyte into the sample tube and seal it with sealing film;

[0152] ② If sufficient electrolyte cannot be collected by method ①, use a hydraulic press (such as the FY-30 hydraulic press of Beijing Hengaode Technology Co., Ltd.) to continuously pressurize until free electrolyte appears, collect the electrolyte into a sample tube and seal it with a sealing film;

[0153] ③If sufficient amount of electrolyte cannot be collected by method ① and method ②, an extraction experiment is required. The specific operation is as follows: add 5g / Ah of a mixture of dichloromethane and cyclohexylbenzene (the volume ratio of the two is 1:9) as an extractant to the battery and record the amount of extractant used. Then put the battery into an aluminum-plastic bag and seal it with a heat sealer. Let it stand at room temperature of 25°C for 4 days to allow the electrolyte in the electrode to be fully mixed with dichloromethane. Then use a pipette to draw the mixture of the extractant and the electrolyte into a 5mL sample tube, and seal the sample tube with sealing film.

[0154] Then, the method of using a nuclear magnetic resonance spectrometer to test whether DMVSP exists in the electrolyte is as follows: 1 mL of the collected electrolyte sample is placed in a sample tube, 0.5 mL of CDCl3 (deuterated chloroform) is taken with a syringe and injected into the sample tube to fully dissolve the sample, and the nuclear magnetic resonance spectrum of the electrolyte is tested using a nuclear magnetic resonance spectrometer (Bruker 400 MHz nuclear magnetic resonance NMR spectrometer), and compared with the DMVSP standard curve (the same test is performed using pure DMVSP to obtain a standard curve) to assist in confirming whether DMVSP exists in the electrolyte.

[0155] If the presence of DMVSP in the electrolyte is measured by a nuclear magnetic resonance spectrometer, the mass proportion of DMVSP in the electrolyte is tested by a gas chromatograph (Thermo Fisher Trace-1610) according to the following method: the collected electrolyte sample is injected into a 2 mL injection bottle using a microinjector, the response curve of the electrolyte sample is tested, and compared with the DMVSP standard curve (the same test is performed using pure DMVSP to obtain the standard curve) to obtain the mass proportion of DMVSP in the electrolyte.

[0156] (2) Contact angle b between the positive electrode active material layer and the solution

[0157] The contact angle meter (JC2000D2M, Beijing Zhongyi Kexin Technology Co., Ltd.) was used for measurement. The specific test method is as follows:

[0158] 1) Positive electrode pretreatment: After disassembling the empty-charged (using the empty-charge method of the test process in which the mass ratio of DMVSP in the electrolyte is a), use ceramic scissors to cut the positive electrode piece of about 8.5*8cm in size. After placing the positive electrode piece at room temperature of 25℃ for 8h, the two ends of the electrode piece can be fixed on the test fixture to start the test;

[0159] 2) Place the device for fixing the electrode on the sample placement table of the contact angle measuring instrument;

[0160] 3) The electrolyte is dripped onto the electrode with a syringe, and the contact angle of the solution when it drops on the electrode for 0.05s is measured, and the contact angle is calculated by a five-point fitting method and an image analysis method; the solution is prepared by mixing ethylene carbonate EC and ethyl methyl carbonate EMC in a mass ratio of 3:7, and adding lithium hexafluorophosphate to adjust the concentration of lithium hexafluorophosphate to 1 mol / L.

[0161] (3) Powder resistivity c of the positive electrode active material layer

[0162] The battery was discharged at 0.33C and disassembled. The positive electrode was placed in a fume hood for 24 hours. Then 1 g of positive electrode powder was collected with a scraper. The scraped positive electrode powder was ball-milled at a speed of 300 r / min. The ball used for ball milling was a zirconia ball with a diameter of 0.6 mm. The ball-to-material ratio was 5:1 and the ball milling time was 20 min. After ball milling, it was placed in a four-probe resistivity tester (ST2722 semiconductor powder resistivity tester of Suzhou Jingge Electronics Co., Ltd.) for powder resistivity test. The specific operation method is as follows: Place the powder on the electrode and pressurize the powder with the other side electrode. Match the pressure strength according to the material. The pressure strength is 10 MPa and read the value of the powder resistivity.

[0163] The performance of the batteries obtained in each embodiment and comparative example was tested. The test results are shown in Table 1. The specific test method is as follows:

[0164] High temperature gas production: charge at a constant current of 0.33C to an upper voltage limit of 3.65V, and charge at a constant voltage until the current is less than or equal to 0.05C. After full charge, use the drainage method to test the volume of the battery, recorded as V0. Then place the battery in a 60℃ oven for 48h. After the battery temperature drops to room temperature of 25℃, use the drainage method to test the battery volume again, recorded as V1. Calculate the 60℃ storage gas production according to the following formula:

[0165] Gas production at 60°C storage = (V1-V0) / battery capacity.

[0166] The specific method of testing the volume of the battery by the drainage method is as follows:

[0167] 1) Add an appropriate amount of pure water into the container and use a density meter to test its density ρ and record it;

[0168] 2) Place the aforementioned container on a balance and peel it (peeling is performed before testing each battery cell);

[0169] 3) Immerse the battery body and the tabs together in pure water to ensure that the battery does not contact the container wall. After stabilization, read and record the data. The data before the battery is stored in the oven is recorded as T0, and the data after the battery is stored in the oven is recorded as T0;

[0170] 4) Turn off the balance and seal the container to prevent the reagent from evaporating.

[0171] V1-V0 is calculated according to the following formula: V1-V0=T1 / ρ-T0 / ρ.

[0172] DCR: Charge the battery to 3.65V at a constant current and voltage of 0.33C, with a cut-off current of 0.05C; leave it for 10 minutes, discharge it to 2.5V at 0.33C, repeat this cycle for 2 cycles, leave it for 10 minutes, charge it to 3.65V at 0.33C, discharge it to 50% SOC of the discharge capacity of the second cycle, leave it for 2 hours, (discharge capacity of the second cycle) discharge at 1C for 18s, record the starting discharge voltage as V3, the voltage after the discharge ends for 18s as V4, the discharge current for 18S as I1, RDCR discharge (I1, 18s) = |V3-V4| / I1.

[0173] Table 1

[0174]

[0175]

[0176]

[0177] For the batteries prepared in the embodiments of the present invention, the DCR is ≤73Ω, and the gas production at 60°C is ≤1.52mL / Ah. It can be seen that the battery containing the positive electrode sheet of the present invention has both low DCR and low gas production.

[0178] It can be seen from the comparison between Examples 1 to 5 and Examples 6 to 9, and between Examples 10 to 11 and Examples 12 to 15 that when the mass proportion a of DMVSP in the electrolyte and the powder resistivity c of the positive electrode active material layer meet the preferred range described in the present invention, it is more conducive to the balance between the DCR and low gas production of the battery.

[0179] It can be seen from the comparison between Examples 1 to 9 and Examples 10 to 17 that when the battery satisfies 0.5≤a×b×c≤16, the balance between the DCR and low gas production of the battery is better.

[0180] According to Comparative Examples 1 to 12, even if the mass proportion a of DMVSP in the electrolyte, the contact angle b between the positive electrode active material layer and the solution, and the powder resistivity c of the positive electrode active material layer are respectively in the appropriate range, when the value of a×b×c exceeds the range of 0.3 to 124 (excluding the two endpoint values), the DCR and gas production of the battery are relatively high.

[0181] It can be seen from Example 22 comparing Example 3 that adding methylene disulfonate to the electrolyte can reduce the amount of DMVSP while obtaining similar DCR and gas production.

[0182] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of this article rather than to limit the scope of protection of this article. Although the present application is described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of this article can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of this article.

Claims

1. A battery, comprising an electrolyte and a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, wherein the positive electrode active material comprises lithium iron phosphate, wherein: The electrolyte comprises tris(dimethylvinylsilyl)phosphate; The battery satisfies the following relationship: 0.3<a×b×c<124, Wherein, a is the mass proportion of the tris(dimethylvinylsilyl)phosphate in the electrolyte; b is the contact angle between the positive electrode active material layer and the solution, in degrees, wherein the solution consists of ethylene carbonate, ethyl methyl carbonate and lithium hexafluorophosphate, wherein the mass ratio of ethylene carbonate to ethyl methyl carbonate is 3:7, and the concentration of lithium hexafluorophosphate in the solution is 1 mol / L; c is the powder resistivity of the positive electrode active material layer, in Ω·cm.

2. The battery according to claim 1, characterized in that The battery satisfies the following relationship: 0.5≤a×b×c≤16.

3. The battery according to claim 1, characterized in that The positive electrode active material layer further includes a lithium supplement additive.

4. The battery according to claim 3, characterized in that The lithium supplement additive includes lithium-rich lithium ferrite.

5. The battery according to claim 1, characterized in that The positive electrode active material also includes at least one of lithium manganese iron phosphate and ternary materials.

6. The battery according to claim 1, characterized in that The c is 1 to 200 Ω·cm, preferably 5 to 50 Ω·cm.

7. The battery according to claim 1, characterized in that The a is 0.0001 to 0.05, preferably 0.001 to 0.

01.

8. The battery according to claim 1, characterized in that The b is 10° to 40°.

9. The battery according to claim 1, characterized in that The battery meets at least one of the following conditions: S1. The particle size Dv50 of the lithium iron phosphate is 0.1 to 2 μm; S2. The compaction density of the positive electrode sheet is 2.0 to 3.0 g / cm 3 ; S3. The electrolyte further comprises methylene disulfonate, wherein the mass ratio of methylene disulfonate in the electrolyte is 0.00001 to 0.05; S4. The battery further comprises a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises graphite, and the particle size Dv50 of the graphite is 5 to 20 μm.

10. An electrical device, characterized in that: The invention comprises the battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium ion battery

    CN114628774A

  • Electrolyte and application thereof

    CN116613377A

  • Novel additive, electrolyte and lithium ion battery

    CN117996188A

  • Lithium ion battery electrolyte and lithium ion battery

    CN118156605A

  • Positive electrode material composition, its method of manufacture, positive electrode sheet containing the same, secondary battery, and power consumption device

    JP2024545195A

Cited By

  • Battery cell, battery assembly and electric device

    WO2026032091A1

  • Battery and electric device

    WO2026143985A1